Corporate Social Responsibility Practices: A Catalyst for Corporate Performance - Oluwakemi O. ONAYEMI; Chinonye L. MOSES; Adewale O. OSIBANJO; Stanley N. AJALIE; Marvellous A.C. GBEREVBIE; Oluwatosin O. ONAYEMI; Ayodeji G. OMOTOLA (Communications of International Proceedings, 2021)
Corporate performance is a subject of concern for both academic and business environment and as a result, there has been a growing interest to focus on how organizations can achieve competitiveness that will ultimately bring about performance. These concerns ranges from managing performance to also effectively and efficiently engaging corporate social responsibility practices in order to bring about corporate performance. As a result of this, this study examined how corporate social responsibility practices can strategically result in corporate performance. Data were collected by using questionnaire, 302 questionnaires were administered to staff of selected manufacturing firms however, 288 were retrieved. Descriptive analysis was used in form of tables in presenting the data. The methodology adopted the chi-square analysis in interpreting the data collected using the SPSS version 21, correlation and cross tabulation method was also used for analyzing and interpreting the data collected Findings showed that corporate social responsibility has a significant effect on corporate performance.
Keywords: Corporate Social Responsibility; Competitiveness; Corporate Performance; Manufacturing firms.